EFFECTIVE PEDAGOGY: CHALLENGES AND SOLUTIONS FOR EARLY GRADE PRIMARY SCHOOL TEACHERS - Masbur Masbur (STAI Nusantara Kota Banda Aceh, 2024)
Teachers in the classroom learning process are considered to play a crucial role in helping students develop a positive attitude toward learning, fostering curiosity, encouraging independence, and promoting intellectual reasoning accuracy, as well as creating conditions for successful learning. There are three fields of knowledge that are closely related to the success of early elementary classroom learning: educational psychology, pedagogy, and educational sociology. The key to a teacher's success in managing the teaching and learning process, particularly in early elementary classrooms, understands the child. Understanding the child means recognizing individual characteristics related to their physical, psychological, and social issues, including their family background. Therefore, one of the most essential areas of knowledge that early elementary teachers need to master is pedagogy. The type of research used in this study is qualitative research. This research involves the examination of concepts and theories from various literature, journals, and books. Developing a conceptual and theoretical framework forms the foundation of this literature or library study. The results of the study reveal: The importance of pedagogical knowledge for early elementary teachers; Understanding the characteristics of early elementary school students; identifying aspects that teachers need to explore in first-grade students, especially concerning individual differences, which include physical, psychological, and social factors.